Teachers’ discourses on young lesbians in the portuguese school context - Rodrigues, Liliana (2015)
This paper aims to analyze teachers’ discourses on young lesbians in the Portuguese schools. To that end, we carried out semi-structured interviews with 24 Portuguese teachers of middle and secondary schools. After having analyzed the retrieved data from the interviews, we identified four main themes: gender polarization; lesbian invisibility; homophobia; and measures against homophobia. Based on their discourses, we concluded that these interviewees have a small amount of knowledge about lesbian women’s sexuality. Despite the legislative progress concerning the Lesbian, Gay, Bisexual and Transgender People's rights in Portugal, teachers are not prepared to deal with this issue both inside and outside the school environment. Furthermore, this research includes some recommendations to deal with homophobia in the Portuguese school context. This study will hopefully contribute to a better understanding of the discourses and practices towards young lesbians in the school panorama, highlighting the importance of promoting non-discriminatory attitudes in the Portuguese schools.